Exploring Adolescents’ Lived Experiences of Social Media Use and Mental Health: A Phenomenological Study from a Psychiatric Nursing Perspective - Zakiyah Mujahidah; Dewa Ayu Saraswati (International Journal of Health and Pharmaceutical (IJHP), 2025)
The rapid expansion of social media has significantly influenced adolescents’ mental health, yet most existing studies rely on quantitative approaches that fail to capture adolescents’ subjective experiences. This study aims to explore adolescents’ lived experiences of social media use and its impact on mental health from a psychiatric nursing perspective. A qualitative study with a phenomenological design was conducted involving 10 high school students in West Jakarta, Indonesia, selected through purposive sampling. Data were collected using semi-structured in-depth interviews and analyzed using thematic analysis following Braun and Clarke’s approach. Data credibility was ensured through member checking. The findings reveal that social media use among adolescents has a dualistic impact. Positive effects include enhanced social connectivity, access to information, and opportunities for self-expression. However, negative impacts are more dominant, including anxiety, stress, depressive feelings, social comparison, sleep disturbances, and decreased concentration. These experiences indicate maladaptive coping mechanisms and emotional vulnerability in navigating digital interactions. Additionally, adolescents demonstrated emerging adaptive strategies such as limiting usage, avoiding negative content, and increasing offline engagement. This study highlights that the impact of social media is not solely determined by usage duration but by how adolescents interpret and manage their digital experiences. Therefore, psychiatric nursing interventions should focus on strengthening digital literacy, emotional regulation, and adaptive coping strategies to promote adolescent mental well-being in the digital era.